2017
DOI: 10.1007/978-3-319-66923-6_35
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Industry 4.0 Concepts and E-learning on Manufacturing Firm Performance: Evidence from Transitional Economy

Abstract: With the application of smart technology concepts, the fourth stage of industrialization, referred to as Industry 4.0, is believed to be approaching. This paper analyzes the extent to which smart factory concepts and e-learning have already deeply affected manufacturing industries in terms of performances in transitional economy. Empirical results indicate that manufacturing companies that have introduce both e-learning and selected smart factory technology concepts differ significantly. E-learning is mainly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…A β-value of 0.397 also shows a positive relationship of smart factories with production and services. These results are in line with the study carried out by Lalic et al (2017). Therefore, the results demonstrate that better implementation of smart factory technologies will lead to higher production and services.…”
Section: Research Findingssupporting
confidence: 90%
“…A β-value of 0.397 also shows a positive relationship of smart factories with production and services. These results are in line with the study carried out by Lalic et al (2017). Therefore, the results demonstrate that better implementation of smart factory technologies will lead to higher production and services.…”
Section: Research Findingssupporting
confidence: 90%
“…However, studies have generally tended to focus on the literature search output or concentrated on individual themes rather than offer a substantive discussion of the key topics, challenges for organisations and implication for theory and industrial practice. Additionally, the trajectory toward I4.0 and all its potential implications, is fast paced and evolving with no one size fits all solution, highlighting the complexities from the I4.0 transition perspective (Ghobakhloo 2018;Haeffner & Panuwatwanich 2017;Lalic et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…tablets, smart phones) [6]. With the use of technological concepts, companies reach higher targets [21]. Russmann et al [22] found that smart factory Industry 4.0 concepts will make production systems as much as 30 percent faster and 25 percent more efficient.…”
Section: Introductionmentioning
confidence: 99%